METHODOLOGY FOR THE FORMATION OF INDEPENDENT ANALYSIS AND ASSESSMENT SKILLS THROUGH INFORMATION AND MEDIA - Tojiboyeva Shokhistakhon Komiljonovna (International Scientific and Current Research Conferences, 2025)
in the context of the speed and diversity of information flow in modern society, the ability of an individual to think critically is important. This article will first look at the theoretical foundations of information and media literacy and highlight the importance of these concepts. The article describes the methodological approaches necessary to access independent analysis processes. The authors also offer effective strategies to teach readers how to evaluate and sort information. They define the main criteria that should be paid attention to when choosing media sources. In addition, among the skills discussed in the article, aspects such as logical thinking, analytical approach and argumentation occupy a special place. Methods are cited that encourage readers to perceive information critically. Also, the possibilities of self-assessment with the help of modern technologies are considered. In general, the article provides innovative approaches aimed at the formation of independent analysis and assessment skills and provides the theoretical knowledge necessary for their practical application. This prepares the younger generation to successfully operate in the global information space.